Economic freedom, development and bank intermediation spreads - Sufian, Fadzlan; Hassan, M. Kabir (Southwestern Economic Society, 2012)
The impact of economic freedom on the well being of the economy has been widely documented in the literature. Noticeably absent is empirical evidence on the influence of economic freedom on cost of financial intermediation. This limitation is somewhat surprising given the fact that the banking sector remains the most important channel for savings and allocations of credit. By using data on the ASEAN-5 banking sectors, the paper attempts to fill in this demanding gap. The results indicate that restrictions on the activities of which banks could undertake reduces their margins. We also find evidence supporting for government interventions contention. However, the impacts of the different dimensions of economic freedom are not uniform across countries with different levels of income.